Anti-semitism in the united states: An overview and strategies to create a more socially just society - Hodge, David R. and Boddie, Stephanie Clintonia (Social Work)
Hate crimes against members of the Jewish community have increased dramatically over the past few years. According to federal data, the number of hate crimes directed at Jews now appears to exceed those directed at many, if not most, minority groups. Yet, despite the number of hate crimes aimed at Jews, little recent scholarship has considered the issue of anti-Semitism. To address this gap in the profession$1 (Bs literature, this article examines the issue of anti-Semitism in the United States. Toward that end, the Jewish population is described and data on anti-Semitism are reviewed along with factors that contribute to this prejudice. The article concludes by discussing strategies that social work educators, practitioners, and researchers might pursue to help create a more socially just society for the Jewish community in the United States and elsewhere. For instance, social workers might seek to address spiritual microaggressions aimed at members of the Jewish community. As part of this process, social workers might help create a culture that respects religious freedom, a fundamental human right, and advocate for equitable portrayals of Jewish people and perspectives in diverse media. Particular attention should be paid to Orthodox Jews, who are often targets of anti-Semitism.- Reproduced s
Keywords: Anti- Semitism, Culture, Discrimination, Hate crimes, Judaism, Religion